2012
DOI: 10.1016/j.jcrs.2012.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Scheimpflug photography–based clinical characterization of the correlation of the corneal shape between the anterior and posterior corneal surfaces in the normal human eye

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
(30 reference statements)
4
25
4
1
Order By: Relevance
“…Conversely, we found no correlation with anterior corneal radius, anterior chamber depth, axial length, anterior corneal astigmatism, and total corneal astigmatism. Significant correlations with posterior corneal radius, horizontal corneal diameter, and central corneal thickness were consistent with the findings of previous reports 5. Regarding the corneal thickness, we estimated that a 100 μm increase in central corneal thickness or a 2.0-mm decrease in horizontal corneal diameter caused an increase of <0.02 in the AP ratio.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, we found no correlation with anterior corneal radius, anterior chamber depth, axial length, anterior corneal astigmatism, and total corneal astigmatism. Significant correlations with posterior corneal radius, horizontal corneal diameter, and central corneal thickness were consistent with the findings of previous reports 5. Regarding the corneal thickness, we estimated that a 100 μm increase in central corneal thickness or a 2.0-mm decrease in horizontal corneal diameter caused an increase of <0.02 in the AP ratio.…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, the ratio of the radius of the anterior corneal curvature to the radius of the posterior corneal curvature (the AP ratio) ranged from 1.132 (the Gullstrand schematic eye model) to 1.235 in the data from Dubbelman et al 24 With the Pentacam, a normal distribution was observed for most of the corneal parameters, and 1.223 was measured at the central 4.0-mm corneal zone for the AP ratio. 22 Monatalbán et al 25 reported an AP ratio of 1.19 with the Pentacam, which is smaller than that for our data (1.217). They showed that a significant, positive correlation existed between the AP shape factor (defined as 1+asphericity) ratio and age, as between the curvatures of the anterior, posterior corneal surfaces and age at 4.5-and 8.0-mm corneal diameters.…”
Section: Discussioncontrasting
confidence: 91%
“…The inverse correlation between k ratio and pachymetry in keratoconus eyes contrasts with the positive correlation found in the normal healthy eyes. 12 Specifically, our research group recently found that thin normal corneas tended to have a steeper anterior corneal surface compared to the posterior corneal surface. Therefore, in keratoconus eyes, the presence of a thinner cornea seems to be in relation with changes in the posterior corneal curvature rather than in the anterior.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, no significant correlation has been found in previous studies between anterior and posterior corneal asphericity in the normal healthy corneas. 12,16 The altered biomechanical properties of the cornea and the susceptibility of the corneal tissue to the stress induced by the intraocular pressure seem to lead to a simultaneous localized steepening in both corneal surfaces, maintaining a correlation of the anterior and posterior geometric profiles. Future studies should evaluate if this level of correlation is different in incipient forms of keratoconus, being a potentially diagnostic tool for this ectatic corneal condition, and the relationship between this level of correlation and the strength of the biomechanical weakening of the cornea.…”
Section: Discussionmentioning
confidence: 99%